Improving the Understanding of Addition and Subtraction of Fractions Through Cooperative Model of Rotating Trio Exchange (RTE) Type for Students Elementary School - Desi Afridayanti; Yeni Rakhmawati; Anismar Anismar (Universitas Negeri Padang, 2022)
The purpose of this research is to improve or help students in mastering the understanding of fractional numbers, especially in addition and subtraction of fractional numbers through a cooperative model, namely the Rotating Trio Exchange (RTE) type. This research is a form of classroom action research with two cycles. The participants or research subjects were our grade V students of SD 95 Pekanbaru which amounted to 33 children. The data collection techniques are observation, interview, documentation, and test. The results of the data analysis were that there were only 14 students or equivalent to 42.43% of students who reached the KKM limit in the initial condition before the research was carried out which was then able to change in cycles 1 to 19 students or around 57.57% which then also rose to 23 students or equivalent to 69.7%. From this description, it can be concluded that the use of the RTE type is able to help students understand and even improve their understanding of the addition and subtraction of fractions. The observation results also illustrate that students' cooperation attitude and responsibility attitudes changed for the better as solid teamwork in the rotation occurred in accordance with the RTE-type learning steps.